Antioxidant Effects of Some Phosphazene Derivatives in Saccharomyces cerevisiae L. Cell Culture Oxidative Stress Model - OZSAHIN, Ayse Dilek; Erdogdu, Ayse; Kirecci, Oguz Ayhan; Aslan, Fatih; Ozturk, Ali Ihsan; Yilmaz, Oekkes (Kahramanmaras Sutcu Imam Univ Rektorlugu, 2023)
In this study, biochemical activities of some phosphazenes were determined in Saccharomyces cerevisiae L. culture medium. Different phosphazene molecules were used in experimental practice. The experimental groups within the scope of the study were organized as control group, H2O2 (Hydrogen peroxide) and groups of phosphazen molecules. After the groups were prepared, 30 mu g of phosphazen and 100 mu l of H2O2 were added to other cultures, except for the control group of S. cerevisiae culture. It was incubated for 72 hours at 30 degrees C. At the end of incubation, cell pellets were separated. Glutathione S-Transferase (GST) and Total protein levels were determined from supernatant. The fatty acid and lipophilic molecules were analyzed from the homogenate obtained with the hexane / isopropanol alcohol mixture. According to our experimental results, while total protein values and GST values increased in parallel with the phosphazen molecule and H2O2 added yeast cells, GST levels were decreased in some groups, although an increase in the amount of protein was observed. Ergosterol, which has an important place in the membrane structure of S. cerevisiae, was found to be higher in T3 and T3B coded phosphazenes and H2O2 groups compared to the control group, and low in T4 coded phosphazenes and H2O2 groups. Our study results revealed that as a result of the addition of phosphazen and H2O2 molecules to the culture medium of S. cerevisiae, ergosterol and fatty acid synthesis, fatty acids cause increases or decreases in the end products of enzymes that double-enter the hydrocarbon chain.
Keywords: Phosphazene; Lipophilic molecules; Saccharomyces cerevisiae L; Fatty acid